2009
DOI: 10.3928/15428877-20090301-23
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Point After Successful Macular Hole Surgery With Internal Limiting Membrane Peeling

Abstract: Scanning laser ophthalmoscope microperimetry facilitated pinpointing of fixation points before and after surgery. The correlation between macular hole size and fixation point shift suggests that the retina around the hole moves centripetally after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Another change in the retinal structure after vitrectomy with ILM peeling is the centripetal movement of the retina around an MH toward the foveal pit after vitrectomy with ILM peeling. 4 However, Kawano et al 5 recently showed a displacement of the macula toward the optic disc, which has been confirmed in latter studies including ours. 6 8 These displacements have been measured relative to the location of the MH, and how these displacements occur relative to the fovea before the development of an MH has not been determined.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another change in the retinal structure after vitrectomy with ILM peeling is the centripetal movement of the retina around an MH toward the foveal pit after vitrectomy with ILM peeling. 4 However, Kawano et al 5 recently showed a displacement of the macula toward the optic disc, which has been confirmed in latter studies including ours. 6 8 These displacements have been measured relative to the location of the MH, and how these displacements occur relative to the fovea before the development of an MH has not been determined.…”
Section: Introductionsupporting
confidence: 83%
“…We were able to obtain SD-OCT images of the preopened MH in these two cases because they had an earlier MH in the fellow eye. Yanagita et al 4 studied 21 cases of an MH, and they reported that the retinal blood vessels near the MH were displaced toward the center of the fovea after a closure of a MH by vitrectomy with ILM peeling. They suggested that the retina around the MH moved toward the foveal pit after the MH surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yanagita et al 13 reported that after a closure of a MH by vitrectomy, the retinal blood vessels near the MH are displaced toward the center of the fovea in all cases. They suggested that the retina around the MH moved toward the foveal pit after vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Yanagita et al reported that the retina around a MH moved toward the foveal pit after vitrectomy [13]. On the other hand, Kawano et al recently showed a displacement of the macula toward the optic disc [14].…”
Section: Introductionmentioning
confidence: 99%